A fractionalcontrolmodeltostudyMonkeypox transportnetwork-relatedtransmission - Zhang, Nan; Emmanuel, Addai; Mezue, MaryNwaife; Rashid, Saima; Akinnubi, Abiola; Abdul-Hamid, Zalia; Asamoah, Joshua Kiddy K. (World Scientific, 2024)
This article is published by World Scientific 2024 and is also available at 10.1142/S179352452450044X